Perspectives on Advancing Countermeasures for Filovirus Disease: Report From a Multisector Meeting - Sprecher, Armand; Cross, Robert; Marzi, Andrea; Martins, Karen A; Wolfe, Daniel; Montgomery, Joel M; Spiropoulou, Christina F; Cihlar, Tomas; Ahuka-Mundeke, Steve; Nyhuis, Tara; Teicher, Carrie; Crozier, Ian; et al. (The Journal of infectious diseases, 2023)
Abstract Although there are now approved treatments and vaccines for Ebola virus disease, the case fatality rate remains unacceptably high even when patients are treated with the newly approved therapeutics. Furthermore, these countermeasures are not expected to be effective against disease caused by other filoviruses. A meeting of subject-matter experts was held during the 10th International Filovirus Symposium to discuss strategies to address these gaps. Several investigational therapeutics, vaccine candidates, and combination strategies were presented. The greatest challenge was identified to be the implementation of well-designed clinical trials of safety and efficacy during filovirus disease outbreaks. Preparing for this will require agreed-upon common protocols for trials intended to bridge multiple outbreaks across all at-risk countries. A multinational research consortium including at-risk countries would be an ideal mechanism to negotiate agreement on protocol design and coordinate preparation. Discussion participants recommended a follow-up meeting be held in Africa to establish such a consortium.